Pelatihan Akuntansi Pemerintahan Bagi Guru Akuntansi Di Kota Dan Kabupaten Jayapura - Sylvia Christina Daat (The Community Engagement Journal, 2019)
State financial reformation, which was followed by the issuance of Accrual-based Government Accounting Standards (SAP), and the Village Law that strongly influenced the teaching skill of government accounting in Indonesia. This development requires the availability of competent human resources to participate directly and actively in managing government finances so that good governance in government sector is achieved. Human Resources who are competent in managing state finances are produced from educational institutions where the teacher is one of the factors that has the most significant contribution. Therefore, in relation to the development of government accounting today, it is necessary to conduct government accounting training for accounting teachers. The implementation of Community Service activities is carried out by using lecture methods, tutorials, and discussions. Activities have been carried out properly as expected. The training activities were carried out with the number of 25 (twenty five) participants in accounting teachers in SMA and SMK in Jayapura City, Jayapura Regency, and Keerom Regency. The training was carried out with tutorial and discussion methods as much as 60% of all training and problem training / practice activities as much as 40%. Participants feel they have benefited from the activities they have carried out.